Bilateral labor agreements and the migration of Filipinos: An instrumental variable approach - Brianna O'Steen (IZA Journal of Development and Migration, 2021)
Bilateral labor agreements (BLAs) are preferred policy models for regulating migration by many governments around the world. The Philippines has been a leader in both agreement conclusion and exporting labor. A recent Congressional evocation is pushing bureaucrats and academics alike to investigate this policy strategy for outcomes and effectiveness. The following analysis answers the question "Do BLAs affect the migration outflows of Overseas Filipino Workers (OFWs)?" using a plausibly exogenous variation to isolate a causal effect. I test for effects of BLAs using two instrumental variables (IVs), such as Bilateral Investment Treaties (BITs) and Formal Alliances, and an original dataset of land-based and sea-based Filipino BLAs and migrant stock in 213 unique areas from 1960 to 2018. I do not find any empirical evidence that these treaties drive migration. However, BLAs have statistically significant effects on gross domestic product (GDP) per capita and exports, suggesting other important channels through which these agreements affect economic outcomes. These null results are critically important for policymakers and diplomats because the resources spent on negotiation are wasted if the primary goal is to increase migration.
Keywords: F220; J610; 330; bilateral labor agreement; migration; Overseas Filipino Workers; labor export; labor policy; Philippines